Analisis Butir Soal Biologi Tipe Hots pada Materi Struktur dan Fungsi Tubuh pada Tingkat Smp - Achmad Alfiyannur Rivanda; Frisda Destriyana Fitaloka (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study presents an analysis of the characteristics of Higher-Order Thinking Skills (HOTS) in the questions found in the chapter on human body structure and function in an eighth-grade textbook aligned with the Merdeka Curriculum used at SMP Muhammadiyah 10 Bandung. The aim of this research is to identify the characteristics of HOTS questions contained in the textbook. The method employed in this study is a descriptive qualitative approach, wherein the content is analyzed by grouping questions categorized as HOTS, analyzing the characteristics of HOTS question types, and categorizing the questions to determine whether they qualify as HOTS. The data is then recorded on an identification sheet. The results indicate that most of the questions meet HOTS criteria, accounting for 68%, while a smaller portion falls under the category of Lower-Order Thinking Skills (LOTS). The HOTS questions take four forms: case excerpts, images, graphs, and tables. This research is expected to contribute to the development of question items that align with the implementation of the Merdeka Curriculum..